Structuring the Thesis 2018
DOI: 10.1007/978-981-13-0511-5_14
|View full text |Cite
|
Sign up to set email alerts
|

Intersections of Indigenous Knowledge and Place Based Education: Possibilities for New Visions of Sustainability Education in Uganda

Abstract: This thesis contains no material which has been accepted for a degree or diploma by the University or any other institution, except by way of background information and duly acknowledged in the thesis, and to the best of my knowledge and belief it contains no material previously published or written by another person except where due acknowledgement is made in the text or the thesis, nor does the thesis contain any material that infringes copyright.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 44 publications
(115 reference statements)
1
3
0
Order By: Relevance
“…The untransformed colonial education system in many previously colonised countries alienates learners from their own places, and this has also been reported by other studies (e.g. Ronoh, 2018;Kezabu et al, 2018). However, as our findings reveal, a critical pedagogy of place can improve students' connection to their environment.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The untransformed colonial education system in many previously colonised countries alienates learners from their own places, and this has also been reported by other studies (e.g. Ronoh, 2018;Kezabu et al, 2018). However, as our findings reveal, a critical pedagogy of place can improve students' connection to their environment.…”
Section: Discussionsupporting
confidence: 88%
“…However, as our findings reveal, a critical pedagogy of place can improve students' connection to their environment. Similarly, Kezabu et al (2018) found that place-based pedagogy reconnected students to their communities, cultures, and places, especially through community service projects undertaken by students, teachers, and elders in a Ugandan community. Also, the inclusion of multiple ways of knowing and connections to communities were found to be effective for learning and the transformation of school curriculum among indigenous peoples (Bang & Medin, 2010;Barnhardt, 2016).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations